2010
DOI: 10.1111/j.1365-3156.2010.02610.x
|View full text |Cite
|
Sign up to set email alerts
|

Sharp injuries and their determinants among health care workers at first-level care facilities in Sindh Province, Pakistan

Abstract: Summaryobjectives To assess the rate and determinants of sharp injuries during the previous 6 months among health care workers at first-level care facilities in two districts of Pakistan.methods Cross-sectional survey at public, general practitioners and non-licensed private practitioners selected through stratified random sampling. At each facility, we interviewed a prescriber and a dispenser ⁄ injection provider about knowledge of bloodborne pathogens transmission and preventive practices, risk perception, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
15
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
8
15
3
3
Order By: Relevance
“…BBPs' transmission Knowledge, being in the job for a longer time and perceiving fewer barriers to safe practice predicts use of UPs in turn resulting in less number of SIs. Similar findings have been reported from previous studies conducted in similar settings from Pakistan and India [Kermode et al, 2005a,b;Janjua et al, 2010b]. Increasing knowledge about BBPs transmission and precautionary measures, and decreasing barriers through easy availability of safety equipment, sharp disposal containers, and providing training on UPs may help the workforce at FLCFs to protect themselves by adopting essential UPs and reducing risk of SIs.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…BBPs' transmission Knowledge, being in the job for a longer time and perceiving fewer barriers to safe practice predicts use of UPs in turn resulting in less number of SIs. Similar findings have been reported from previous studies conducted in similar settings from Pakistan and India [Kermode et al, 2005a,b;Janjua et al, 2010b]. Increasing knowledge about BBPs transmission and precautionary measures, and decreasing barriers through easy availability of safety equipment, sharp disposal containers, and providing training on UPs may help the workforce at FLCFs to protect themselves by adopting essential UPs and reducing risk of SIs.…”
Section: Discussionsupporting
confidence: 88%
“…We found that when UPs score was included in the model, none of the constructs of HBM were significant while in a model without UPs score two constructs of HBMbarriers to safe practice and perceived severity of disease as a result of SIs, were significant. This further clarified the earlier findings from Pakistan and India and confirms that UPs is an intermediate between SIs and different behavioral predictors including some of the constructs of HBM [Kermode et al, 2005a;Janjua et al, 2010b]. In other words, these constructs work through the use of UPs in reducing SIs.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The logistic regression model in this study found that greater work experience, > 14 years of schooling, having ≤ 20 patients per day, administering < 30 injections per day and not recapping needles or reusing syringes were significantly associated with lower risk of sharps injury. The inverse relationship between work experience and sharps injury is consistent with previous studies conducted at primary care facilities in Pakistan [23,24] and India [8]. The exact reason for the lower risk of sharps injury with increased work experience is unknown; however, the most likely explanation for this association could be attainment of greater skill in carrying out procedures such as injection administration, suturing and cannulation over time.…”
Section: Discussionsupporting
confidence: 79%